Predicting High School Students' Problematic Internet Use in Terms of Religious Beliefs and Moral Maturity - EKŞİ, HALİL (TURKISH GREEN CRESCENT SOC, 2017)
This study intends to reveal the relationships among high school students' problematic Internet use with their religious beliefs and moral maturity. Data has been collected using the Problematic Internet-Use Scale, Religious Belief Scale, Moral Maturity Scale, and personal information form; the participants consist of 389 high school students. The results of the analysis obtained by multiple linear regression analysis reveals that moral maturity is a significant predictor of problematic Internet use in high school students; no statistically significant relationship exists between students' level of religious belief and problematic Internet use. Therefore, individuals' moral maturity is considered as an important contribution for future studies and for guidance and counseling services in preventing problematic Internet use.
Keywords: Problematic Internet use; Religious belief; Moral maturity; High school student; Internet; ADDICTION; ADOLESCENTS; DEPRESSION; FEATURES